Targeting the PI3K/mTOR Pathway in Pediatric Hematologic Malignancies - Tasian, Sarah K.; Teachey, David T.; Rheingold, Susan R. (Frontiers in Oncology, 2014)
A complex interplay of intracellular signaling networks orchestrates normal cell growth and survival, including translation, transcription, proliferation, and cell cycle progression. Dysregulation of such signals occurs commonly in many malignancies, thereby giving the cancer cell a survival advantage, but also providing possible targets for therapeutic intervention. Activation of the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling pathway contributes to the proliferative advantage of malignant cells and may confer resistance to chemotherapy in various hematologic malignancies. The initial mTOR inhibitor, sirolimus (also known as rapamycin), was first discovered in 1975 in the soil of Easter Island. Sirolimus was originally developed as an anti-fungal agent given its macrolide properties, but was approved by the Food and Drug Administration (FDA) in 1999 as an immunosuppressive agent for renal transplantation patients once its T cell suppression characteristics were recognized. Shortly thereafter, recognition of sirolimus’s ability to inhibit cellular proliferation and cell cycle progression brought sirolimus to the forefront as a possible inhibitor of mTOR. In the subsequent decade, the functional roles of the mTOR protein have been more fully elucidated, and this protein is now known to be a key regulator in a highly complex signaling pathway that controls cell growth, proliferation, metabolism, and apoptosis. This article discusses the dysregulation of PI3K/mTOR signaling in hematologic malignancies, including acute and chronic leukemias, lymphomas, and lymphoproliferative disorders. The current repertoire of PI3K/mTOR pathway inhibitors in development and clinical trials to date are described with emphasis upon pediatric hematologic malignancies (Figure 1). Investigation of small molecule inhibitors of this complex signaling network is an active area of oncology drug development.